2014
DOI: 10.1152/ajprenal.00353.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and carbon monoxide antagonize TGF-β through ligand-independent internalization of TβR1/ALK5

Abstract: Transforming growth factor (TGF)-β plays a central role in vascular homeostasis and in the pathology of vascular disease. There is a growing appreciation for the role of nitric oxide (NO) and carbon monoxide (CO) as highly diffusible, bioactive signaling molecules in the vasculature. We hypothesized that both NO and CO increase endocytosis of TGF-β receptor type 1 (TβR1) in vascular smooth muscle cells (VSMCs) through activation of dynamin-2, shielding cells from the effects of circulating TGF-β. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Moreover, it has been reported that HMOX-1 derived metabolites including CO activated the mitochondrial function of astrocytes via HIF-1α/estrogen-related receptor α (ERRα) circuit and therefore play an important role in the repair of neurovascular function after ischemic brain injury [65]. Additionally, CO has been suggested as a protective factor limiting the profibrotic effects of TGF-β in the vasculature [66]. The components of HMOX-1/CO pathway have been shown in hepatocellular carcinoma cells to confer their resistance to TGF-β-mediated growth inhibition by increasing Smad3 phosphorylation via the ERK1/2 pathway [67].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that HMOX-1 derived metabolites including CO activated the mitochondrial function of astrocytes via HIF-1α/estrogen-related receptor α (ERRα) circuit and therefore play an important role in the repair of neurovascular function after ischemic brain injury [65]. Additionally, CO has been suggested as a protective factor limiting the profibrotic effects of TGF-β in the vasculature [66]. The components of HMOX-1/CO pathway have been shown in hepatocellular carcinoma cells to confer their resistance to TGF-β-mediated growth inhibition by increasing Smad3 phosphorylation via the ERK1/2 pathway [67].…”
Section: Discussionmentioning
confidence: 99%
“…GDNF is a member of the TGFβ superfamily and we found that it could induce HSC activation. TGFβ is mediating its multifunctional effects on liver cells by binding to ALK5 39, 40 followed by subsequent downstream signalling via phosphorylation and nuclear translocation of Smad2/3 to regulate target gene expression in a context-dependent manner. 41 Thus, we hypothesised that GDNF might involve ALK5 to induce HSC activation.…”
Section: Discussionmentioning
confidence: 99%
“…downregulated gastric mucosal mRNA expression for anti-inflammatory Anxa1 , upregulated mucosal mRNA expression for Tgfbr2 and r3 and maintained elevated TGFB1 and TGFB2 serum concentration in rats administered with ethanol. It has been previously reported that CORM-2 can antagonize TGFB activity through internalization of TGFB receptor 1 (ALK5) inhibiting profibrotic effect of this inflammatory factor 102 . However, we observed that Anxa1 mRNA expression was decreased in rats administered with high dose of aspirin but pretreatment with BW-CO-111 increased the gastric mucosal mRNA expression for this protein and similarly to rats administered with ethanol, this CO-prodrug maintained elevated TGFB1 and TGFB2 serum contents and maintained upregulated mucosal mRNA expression for Tgfbr3 by aspirin.…”
Section: Discussionmentioning
confidence: 99%